2014
DOI: 10.1021/np500198g
|View full text |Cite
|
Sign up to set email alerts
|

Tetra- and Pentacyclic Triterpene Acids from the Ancient Anti-inflammatory Remedy Frankincense as Inhibitors of Microsomal Prostaglandin E2Synthase-1

Abstract: The microsomal prostaglandin E2 synthase (mPGES)-1 is the terminal enzyme in the biosynthesis of prostaglandin (PG)E2 from cyclooxygenase (COX)-derived PGH2. We previously found that mPGES-1 is inhibited by boswellic acids (IC50 = 3–30 μM), which are bioactive triterpene acids present in the anti-inflammatory remedy frankincense. Here we show that besides boswellic acids, additional known triterpene acids (i.e., tircuallic, lupeolic, and roburic acids) isolated from frankincense suppress mPGES-1 with increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…Boswellic acids are inhibitors of 5-lipoxygenase, but had little effect on COX-2 (Verhoff et al, 2014). As an important role in the inflammatory responses of inflammatory cells and tissues, COX-2 inhibition exerts potent anti-inflammatory and analgesic effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boswellic acids are inhibitors of 5-lipoxygenase, but had little effect on COX-2 (Verhoff et al, 2014). As an important role in the inflammatory responses of inflammatory cells and tissues, COX-2 inhibition exerts potent anti-inflammatory and analgesic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Boswellic acids in the resinous part are inhibitors of 5-lipoxygenase and thought to be responsible for anti-inflammatory activity (Verhoff et al, 2014); the gum portion may contribute to anti-oxidative effects (Batista et al, 2010); and the essential oil, a mixture of terpenes and sesquiterpenes or their derivatives, has anti-tumor (Singh et al, 2008) and antibacterial activities (Batista et al, 2010). More than three hundred volatiles have been identified in the essential oil, common compounds were α-pinene, 1-octanol, linalool, limonene, octyl acetate, α-thujene, and (E)-β-ocimene et al (Pan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…mPGES-1 as target of these NPs may provide a basis for their antiinflammatory properties and rationalize their use in folk medicine as remedy for treatment of inflammatory disorders. Among these plant-derived mPGES-1 inhibitors are prominent antiinflammatory and anti-tumoral compounds like the polyphenol curcumin from turmeric [86], epigallocatechin-3-gallate (EGCG) from green tea [87], the acylphloroglucinol hyperforin from St. John´s wort [66] and garcinol from Garcinia indica [88], triterpene acids from frankincense (e.g., tirucallic acids, lupeolic acids, boswellic acids,) [89,90], the diterpenoids carnosol and carnosic acid from Salvia officinalis [91], and the quinone embelin from Embelia ribes [92]. All of them inhibit mPGES-1 in cell-free assays in the submicromolar range (Table 1).…”
Section: Inhibitors Have Been Reported Yetmentioning
confidence: 99%
“…One of these traditional remedies is olibanum. Olibanum (frankincense) is a resin obtained from trees of the genus Boswellia in the family Burseraceae and has been used in traditional remedies for decades [2]. This precious material has been traded on the Arabian peninsula for more than 5000 years, and it has been used in the traditional medicines of India, Africa, China but also in Western countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…The resin contains different types of secondary metabolites, such as di-, sesqui-and triterpenes but also essential oils [2,15]. Among all of these, triterpenoids [16] are the most abundant, and many studies have shown among other effects the cytotoxic and antitumor properties of triterpenoids from frankincense.…”
Section: Introductionmentioning
confidence: 99%